2018
DOI: 10.1257/app.20170048
|View full text |Cite
|
Sign up to set email alerts
|

Do Risk Preferences Change? Evidence from the Great East Japan Earthquake

Abstract: We investigate whether individuals' risk preferences change after experiencing a natural disaster, specifically, the 2011 Great East Japan Earthquake. Exploiting the panels of nationally representative surveys on risk preferences, we find that men who experienced greater intensity of the earthquake became more risk tolerant a year after the Earthquake. Interestingly, the effects on men's risk preferences are persistent even five years after the Earthquake at almost the same magnitude as those shortly after the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
155
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(165 citation statements)
references
References 94 publications
(118 reference statements)
7
155
2
1
Order By: Relevance
“…In addition to providing information, natural disasters can affect risk aversion, which, in turn, can affect insurance demand (Outreville 2014, Petrolia et al 2015), although evidence is mixed regarding the direction. Although some studies report an increase in risk seeking behavior after exposure to natural disasters (Eckel, El Gamalb, and Wilson 2009;Page et al 2014;Hanaoka, Shigeoka, and Watanabe 2018), others find the opposite (Cameron and Shah 2015;Cassar, Healy, and Von Kessler 2017). In insurance markets, it has been observed that take-up rates of flood insurance increase right after a disaster event and then decline (Gallagher 2013;Atreya, Ferreira, and Michel-Kerjan 2015).…”
Section: Market Penetration and Individual Choice Under Risk: Moving mentioning
confidence: 99%
“…In addition to providing information, natural disasters can affect risk aversion, which, in turn, can affect insurance demand (Outreville 2014, Petrolia et al 2015), although evidence is mixed regarding the direction. Although some studies report an increase in risk seeking behavior after exposure to natural disasters (Eckel, El Gamalb, and Wilson 2009;Page et al 2014;Hanaoka, Shigeoka, and Watanabe 2018), others find the opposite (Cameron and Shah 2015;Cassar, Healy, and Von Kessler 2017). In insurance markets, it has been observed that take-up rates of flood insurance increase right after a disaster event and then decline (Gallagher 2013;Atreya, Ferreira, and Michel-Kerjan 2015).…”
Section: Market Penetration and Individual Choice Under Risk: Moving mentioning
confidence: 99%
“…6 See Blattman and Miguel (2010) for a review of the literature on exposure to violence, and Voors, Nillesen, Verwimp, Bulte, Lensink, and van Soest (2012), Bauer, Cassar, Chytilová, and Henrich (2014), Cassar, Grosjean, and Whitt (2013), or Jakiela and Ozier (2019) for more recent contributions. On natural disasters, see Cameron and Shah (2015), Cassar, Healy, and von Kessler (2017), and Hanaoka, Shigeoka, and Watanabe (2018). On economic shocks, c.f.…”
Section: Introductionmentioning
confidence: 99%
“…Although different in nature to events studied here,Hanaoka et al (2018) find that men in areas more affected by an earthquake in Japan became less risk averse, while women's preferences were not affected.22 For example, the overall OR for a male who experienced a financial improvement 0-3 months ago is 1.362 × 0.834 = 1.136.…”
mentioning
confidence: 62%
“…Sahm, 2012;Salamanca, 2016). On the other hand, evidence of a deterministic component comes from research that links shifts in risk preferences to significant natural events such as hurricanes, floods, earthquakes and tsunamis (Eckel et al, 2009;Page et al, 2014;Cameron & Shah, 2015;Said et al, 2015;Cassar et al, 2017;Hanaoka et al, 2018) as well as more frequent life experiences such as health shocks (Decker & Schmidtz, 2016), exposure to violent crime and conflict (Voors et al, 2012;Brown et al, 2017), parenthood (Görlitz & Tamm, 2015;Browne et al, 2016) and changes in financial circumstances (Anderson et al, 2008). People also appear to become more risk averse as they get older (e.g.…”
Section: Introductionmentioning
confidence: 99%